Husserl - Bell, David, 1947 April 24- (London ; New York : Routledge, 1999)
One of the most important and influential philosophers of the 20th century, up to now Edmund Husserl's influence has been restricted largely to the ""continental"" philosophical tradition. In this critical examination of Husserl's philosophy, David Bell introduces those who work in the broadly ""analytic"" tradition to the arguments and ideas of this fascinating thinker. Bell considers Husserl's philosophy as a whole, tracing its origins in Brentano's teachings, and the way it developed from the earliest writings on logic to the last works on culture and the ""Lebenswelt"". He also shows how H.
Chapter Prolegomenon: Brentano's Legacy -- part Part I Naturalism -- chapter I The Philosophy of Arithmetic -- chapter II Logical Investigations -- part Part II Transcendental Idealism -- chapter III Solipsistic Idealism -- chapter IV The Indivdual and The Lebenswelt.
Originally published: 1990.
Includes bibliographical references (pages 252-263) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Husserl, Edmund, -- 1859-1938.; Husserl, Edmund, -- 1859-1938; PHILOSOPHY -- History & Surveys -- Modern; Humaniora -- Filosofi